Blame and Severity Attributions in Vignette-Based Female-On-Male Rape: The Case of the Victim’s Prior Sexual Victimization, Resistance, and Sexual Arousal - Tomer, Einat (International journal of offender therapy and comparative criminology, 2025)
This study examines blame attributions of victims and perpetrators in female-on-male rape cases and event severity attributions as affected by three victim-related variables: prior sexual victimization, resistance during the rape, and sexual arousal during the rape. It assesses the relative weight of each of these variables in determining the attribution of blame to the victim and perpetrator and the attribution of severity to the event. The study found that sexual arousal and absence of resistance correlated with higher victim blame attribution, lower perpetrator blame, and lower event severity attributions, while prior sexual victimization had the opposite correlations. We therefore conclude that blame and severity attributions are affected by the victim’s behavior prior to the rape and during the rape.